EFFECTIVE WAYS OF TEACHING GRAMMAR IN ELEMENTARY SCHOOL CHILDREN (Ustozlar uchun, 2026)
This article explores the pedagogical and methodological foundations of teaching grammatical concepts during mother tongue and literacy lessons in primary education. The primary objective is to demonstrate ways to develop grammatical competencies through logical and interactive methods, moving away from rote memorization while considering the cognitive developmental stages of young learners. The study analyzes the effectiveness of game-based technologies, visualization, and inductive approaches. The findings indicate that visual and contextual teaching significantly improves students' literacy levels and their ability to apply rules in practical writing.